The Regenerative Potential of bFGF in Dental Pulp Repair and Regeneration - Liu, Keyue; Yu, Sijing; Ye, Ling; Gao, Bo (Frontiers in Pharmacology, 2021)
Regenerative endodontic therapy intends to induce the host’s natural wound-healing process, which can restore the vitality, immunity, and sensitivity of the inflammatory or necrotic pulp tissue destroyed by infection or trauma. Myriads of growth factors are critical in the processes of pulp repair and regeneration. Among the key regulatory factors are the fibroblast growth factors, which have turned out to be the master regulators of both organogenesis and tissue homeostasis. Fibroblast growth factors, a family composed of 22 polypeptides, have been used in tissue repair and regeneration settings, in conditions as diverse as burns, ulcers, bone-related diseases, and spinal cord injuries. Meanwhile, in dentistry, the basic fibroblast growth factor is the most frequently investigated. Thereby, the aim of this review is 2-fold: 1) foremost, to explore the underlying mechanisms of the bFGF in dental pulp repair and regeneration and 2) in addition, to shed light on the potential therapeutic strategies of the bFGF in dental pulp–related clinical applications.